Introduction to the Special Issue: European Contributions to Strong Reflexivity. (November 2016) - Kuehner, Angela; Ploder, Andrea; Langer, Phil C.
This special issue is devoted to reflexivity as an epistemic tool in qualitative research. We suggest a distinction between epistemically weak and epistemically strong reflexivity and present examples for strongly reflexive research from the German-speaking countries and the United Kingdom. The issue pursues three major goals: First, it provides a vocabulary to deepen the discussion about the epistemic dimensions of reflexivity. Second, it intervenes in hegemonic discourses on the "threat of subjectivity" and shows that approaches often perceived as "more subjective" and therefore less valid use, in fact, an epistemically stronger concept of reflexivity. Third, it offers insight into some innovative areas of strongly reflexive research in Europe. A comparison of these methodologies shows that the use of reflexivity as an epistemic tool is compatible with a wide range of approaches.